Vascular Reconstruction of Multiple Renal Arteries—A Risk Factor for Transplant Renal Artery Stenosis: Insight From a Matched Case-Control Study - Devprakash Choudhary; Rajesh Vijayvergiya; Kamal Kishore; Vanji Nathan Subramani; Mohan Banoth; Sai Praneeth Reddy Perugu; Milind Mandwar; Bharat Bamaniya; Arun Panjathia; Parul Gupta; Shiva Kumar S. Patil; Jasmine Sethi; et al. (Transplant International)
Transplant Renal Artery Stenosis (TRAS) is the leading vascular complication following kidney transplantation (KT), causing premature allograft loss and increased post-KT mortality. While risk factors for TRAS, such as prolonged cold ischemia time and delayed graft function, are well-documented in deceased donor-KT, the risk factors remain less clearly defined in living donor-KT. This matched case-control study, conducted at a leading national transplant center predominantly performing living donor-KT, evaluated risk factors and long-term outcomes of clinical TRAS (cTRAS). cTRAS cases diagnosed from January 2009 to December 2022 were matched with four control kidney transplant recipients (KTRs) in a study powered to assess whether ex-vivo arterial vascular reconstruction of multiple renal arteries (VR-MRA) increases the risk of cTRAS. Among 2,454 KTs, 28 KTRs (1.14%) were diagnosed with cTRAS around 3.62 ± 1.04 months post-KT, with renal allograft dysfunction (92.86%) as the most common presenting feature. Notably, 27 cTRAS cases were successfully treated with endovascular intervention, yielding favorable outcomes over a 6–180 months follow-up period. The study identified ex-vivo VR-MRA as an independent risk factor for cTRAS (P < 0.001). cTRAS cases receiving timely treatment exhibited long-term outcomes in graft and patient survival similar to control KTRs. Early screening and timely intervention for cTRAS post-KT may improve graft and patient outcomes.